Pasta, pizza and propaganda : a political history of Italian food TV - Buscemi, Francesco (Trajectories in Italian cinema and media., 2022)
A lively and rigorous historical account of Italian food television narrated from a political point of view. In referring to the sociology of Pierre Bourdieu, the book links food, television and politics and shows how the three give way to the political construction of various versions of Italy, from 1954 to the present. 12 b/w photographs.